Neighborhood street scale elements, sedentary time and cardiometabolic risk factors in inactive ethnic minority women. - Rebecca E Lee; Scherezade K Mama; Heather J Adamus-Leach (PLoS ONE, 2012)
Cardiometabolic risk factors such as obesity, excess percent body fat, high blood pressure, elevated resting heart rate and sedentary behavior have increased in recent decades due to changes in the environment and lifestyle. Neighborhood micro-environmental, street scale elements may contribute to health above and beyond individual characteristics of residents.To investigate the relationship between neighborhood street scale elements and cardiometabolic risk factors among inactive ethnic minority women.Women (N = 410) completed measures of BMI, percent body fat, blood pressure, resting heart rate, sedentary behavior and demographics. Trained field assessors completed the Pedestrian Environment Data Scan in participants' neighborhoods. Data were collected from 2006-2008. Multiple regression models were conducted in 2011 to estimate the effect of environmental factors on cardiometabolic risk factors.Adjusted regression models found an inverse association between sidewalk buffers and blood pressure, between traffic control devices and resting heart rate, and a positive association between presence of pedestrian crossing aids and BMI (ps<.05). Neighborhood attractiveness and safety for walking and cycling were related to more time spent in a motor vehicle (ps<.05).Findings suggest complex relationships among micro-environmental, street scale elements that may confer important cardiometabolic benefits and risks for residents. Living in the most attractive and safe neighborhoods for physical activity may be associated with longer times spent sitting in the car.